ANALYSIS OF HUMAN STRUGGLE OF MAIN CHARACTERS IN INDIAN DRAMA FILM “BLACK” (2005) - Tira Nur Fitria (LET: Linguistics, Literature and English Teaching Journal, 2022)
This study describes the struggle of the main characters in the Black movie. This study is descriptive qualitative. The analysis shows that 1) Sahai convinces Michelle's parents, especially her father to help Michelle. 2) Sahai controls Michelle's emotional disturbance by ignoring her anger and refusing to speak through finger-spelling. 3) Sahai teaches fingerspelling by touching and forming letters on Michelle's hand. 4) Sahai teaches Michelle good manners in eating with a spoon. The impact of Sahai's struggle on Michelle's life is 1) Michelle can spell letters and words. 2) Michelle gets a college education and can graduate. 3) She can become fully human is physically limited. The film shows human struggle trapped in the darkness that surrounds Michelle's life makes her behave like an animal because she can't catch and understand the teachings and attention of her parents. Michelle as a disabled child since birth, can't see and hear, which makes her mother look for a teacher to educate her. Sahai teaches her how to communicate through hand and mouth gestures. So, we can understand the struggles of the parents, teacher, and Michelle's struggle to find light in her life.